Therapeutic Molecular Phenotype of β-Blocker–Associated Reverse-Remodeling in Nonischemic Dilated Cardiomyopathy. (April 2015) - Kao, David P.; Lowes, Brian D.; Gilbert, Edward M.; Minobe, Wayne; Epperson, L. Elaine; Meyer, Leslie K.; Ferguson, Debra A.; Volkman, Ann Kirkpatrick; Zolty, Ronald; Borg, C. Douglas; Quaife, Robert A.; Bristow, Michael R.
<x xml:space="preserve">Abstract</x> Background— When β-blockers produce reverse-remodeling in idiopathic dilated cardiomyopathy, they partially reverse changes in fetal–adult/contractile protein, natriuretic peptide, SR-Ca2+-ATPase gene program constituents. The objective of the current study was to further test the hypothesis that reverse-remodeling is associated with favorable changes in myocardial gene expression by measuring additional contractile, signaling, and metabolic genes that exhibit a fetal/adult expression predominance, are thyroid hormone-responsive, and are regulated by β1-adrenergic receptor signaling. A secondary objective was to identify which of these putative regulatory networks is most closely associated with observed changes. Methods and Results— Forty-seven patients with idiopathic dilated cardiomyopathy (left ventricular ejection fraction, 0.24±0.09) were randomized to the adrenergic-receptor blockers metoprolol (β1-selective), metoprolol+doxazosin (β1/α1), or carvedilol (β1/β2/α1). Serial radionuclide ventriculography and endomyocardial biopsies were performed at baseline, 3, and 12 months. Expression of 50 mRNA gene products was measured by quantitative polymerase chain reaction. Thirty-one patients achieved left ventricular ejection fraction reverse-remodeling response defined as improvement by ≥0.08 at 12 months or by ≥0.05 at 3 months (Δ left ventricular ejection fraction, 0.21±0.10). Changes in gene expression in responders versus nonresponders were decreases in NPPA and NPPB and increases in MYH6, ATP2A2, PLN, RYR2, ADRA1A, ADRB1, MYL3, PDFKM, PDHX, and CPT1B. All except PDHX involved increase in adult or decrease in fetal cardiac genes, but 100% were concordant with changes predicted by inhibition of β1-adrenergic signaling. Conclusions— In addition to known gene expression changes, additional calcium-handling, sarcomeric, adrenergic signaling, and metabolic genes were associated with reverse-remodeling. The pattern suggests a fetal–adult paradigm but may be because of reversal of gene expression controlled by a β1-adrenergic receptor gene network. Clinical Trial Registration— URL: www.clinicaltrials.gov. Unique Identifier: NCT01798992.